Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(1,=x\left(x^2-2x+1-y^2\right)=x\left[\left(x-1\right)^2-y^2\right]=x\left(x-y-1\right)\left(x+y-1\right)\\ 2,=\left(x+y\right)^3\\ 3,=\left(2y-z\right)\left(4x+7y\right)\\ 4,=\left(x+2\right)^2\\ 5,Sửa:x\left(x-2\right)-x+2=0\\ \Leftrightarrow\left(x-2\right)\left(x-1\right)=0\Leftrightarrow\left[{}\begin{matrix}x=1\\x=2\end{matrix}\right.\)
\(x^2-x-xy-2y^2+2y\)
\(=x^2-x-2xy+xy-2y^2+2y\)
\(=\left(-2y^2-2xy+2y\right)+\left(xy+x^2-x\right)\)
\(=2y\left(-y-x+1\right)-x\left(-y-x+1\right)\)
\(=\left(2y-x\right)\left(-y-x+1\right)\)
`a^3-a^2 x -ay+xy`
`=a^2(a-x)-y(a-x)`
`=(a-x)(x^2-y)`
`x^2-2xy+x-2y`
`= (x^2+x)-(2xy+2y)`
`=x(x+1)-2y(x+1)`
`=(x+1)(x-2y)`
`x^2-2x+2y-xy`
`=x(x-2) + y(2-x)`
`=x(x-2)-y(x-2)`
`=(x-2)(x-y)`
\(x^2+xy-2y^2=x^2-xy+2xy-2y^2\)
\(=x\left(x-y\right)+2y\left(x-y\right)\)
\(=\left(x-y\right)\left(x+2y\right)\)
\(x^3-x^{22}-xy^2+y^2\)
\(=x^2\left(x-1\right)-y^2\left(x-1\right)\)
\(=\left(x^2-y^2\right)\left(x-1\right)\)
\(=\left(x-y\right)\left(x+y\right)\left(x-1\right)\)
=xy(x-y)
HT nha bn